2009
DOI: 10.4161/derm.1.3.8496
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuropeptides in the multifactorial pathogenesis of acne vulgaris

Abstract: Background: Central or peripheral stress may induce the development of clinical inflammation in the pilosebaceous unit (PSU) leading to the development or to exacerbation of preexisting acne. The presence of a complete corticotropin-releasing hormone (CRH) system has been confirmed in human sebocytes in vitro. CRH is capable to induce lipid synthesis, steroidogenesis and interact with testosterone and growth hormone. α-Melanocyte-stimulating hormone (α-MSH) and its receptors can regulate melanogenesis as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 47 publications
(60 reference statements)
1
42
0
10
Order By: Relevance
“…Increased α-MSH and MC-1R expression in sebaceous glands has been shown in patients with acne in the case of systemic or cutaneous stress. The α-MSH / MC1R interaction has been suggested to be closely related to keratinocyte proliferation and differentiation [14]. In this study, it was observed that SRS amplitude and latency values of AV patients were not different from healthy controls.…”
Section: Discussionsupporting
confidence: 51%
“…Increased α-MSH and MC-1R expression in sebaceous glands has been shown in patients with acne in the case of systemic or cutaneous stress. The α-MSH / MC1R interaction has been suggested to be closely related to keratinocyte proliferation and differentiation [14]. In this study, it was observed that SRS amplitude and latency values of AV patients were not different from healthy controls.…”
Section: Discussionsupporting
confidence: 51%
“…Так, Ganceviciene и соавт. в 2009 г. было показано, что в сальных железах больных с акне значительно больше рецепторов к основным гормонам стресса, гонадотропин-рилизинг гормону и меланоцит-стимулирующему гормону, чем в сальных железах здоро-вых добровольцев [5].…”
Section: педиатрическая фармакологияunclassified
“…ЛИЧНОСТНЫЕ И ПСИХИЧЕСКИЕ ОСОБЕННОСТИ ДЕТЕЙ И ПОДРОСТКОВ С УГРЕВОЙ БОЛЕЗНЬЮ В подавляющем большинстве случаев угревая сыпь не представляет угрозы для жизни, но при этом ее нали-чие значительно снижает качество жизни [5]. Психо-эмоциональный стресс, связанный с косметическим дефектом, наиболее выражен у лиц подросткового воз-раста [18].…”
Section: педиатрическая фармакологияunclassified
“…However, in lesional skin of patients with acne, another common dermatosis, intra-cellular upregulation of CRH was detected (23). CRH upregulates 3b-HSD at the mRNA level in human SZ95 sebocytes, thus promoting lesional steroidogenesis and subsequently androgen excess, which is known to be one of the major pathophysiological factors of the disease (24).…”
Section: Accepted For Publication 18 July 2014mentioning
confidence: 99%